TINJAUAN STANDAR PELAYANAN MINIMAL REKAM MEDIS DI RUMAH SAKIT SUMBER WARAS KABUPATEN CIREBON - Pujairah Pitaloka; Ani Nurhaeni; Hendri Rosmawan (Jurnal Kesehatan Mahardika, 2019)
Background. Medical record service is a professional supporting activity oriented to health information needs organized according to minimum service standards based on regulation number 129 of the year 2008. Purpose. The purpose of this study is to find out the minimum standard of medical record services at Sumber Waras Hospital, Cirebon Regency. Method. The research design used was descriptive research. Data collection techniques using the observation method with the research instrument used is a checklist sheet. Data collection procedures are carried out by determining inclusion and exclusion criteria. Sampling in this study uses quota sampling. Result. The results showed that completeness of filling in inpatient medical record documents had 22 documents (73%) complete and 8 documents (27%) incomplete. Completeness of inpatient informed consent was obtained as many as 22 documents (73%) complete and 8 documents (27%) were incomplete. The time to provide medical record documents for outpatient services is provided quickly as many as 13 documents and slow as many as 17 documents. Conclusions. The conclusions obtained in this study are, the minimum standard of medical record service at Sumber Waras Hospital, Cirebon Regency is not in accordance with the Decree of the Minister of Health number 129 of 2008.